2017
DOI: 10.1016/j.joms.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Surgical Planning for Inferior Alveolar Nerve Reconstruction

Abstract: Despite perceived prejudice against simultaneous IAN reconstruction with complex mandibular resection and reconstruction, the use of IAN VSP may facilitate the actual surgical procedure and result in considerably improved patient outcomes without considerable additional time or cost associated with this protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 10 publications
0
15
0
2
Order By: Relevance
“…Recent studies have shown time-cost benefits in orthognathic surgery 9,12,14 and free flap and graft reconstruction. 1,3,5,6,[15][16][17] The method described in this study has the potential to be expanded to those areas of oral and maxillofacial surgery as well, which could result in decreased costs and less delay before surgery.…”
Section: E5mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown time-cost benefits in orthognathic surgery 9,12,14 and free flap and graft reconstruction. 1,3,5,6,[15][16][17] The method described in this study has the potential to be expanded to those areas of oral and maxillofacial surgery as well, which could result in decreased costs and less delay before surgery.…”
Section: E5mentioning
confidence: 99%
“…particular, has the potential to drastically reduce operating room (OR) time and OR costs. 1,3,5,6,12 Currently, several corporations are contracted with maxillofacial plating companies to provide 3D planning and printing of surgical models, stents, and guides to facilitate surgery. However, these services can be cost prohibitive and can require a considerable lead time.…”
mentioning
confidence: 99%
“…A pesar de que actualmente hay mejoras en las técnicas quirúrgicas y del uso de planificación virtual en cirugía maxilofacial, siguen ocurriendo lesiones de los NAI y NL (10,20,21) . Debido a la naturaleza de las lesiones de estos nervios es importante considerar la reconstrucción microquirúrgica para optimizar la RSF y la calidad de vida del paciente (1) .…”
Section: Discussionunclassified
“…Aunque los conductos pueden tener una indicación limitada en la reconstrucción para brecha nerviosa, varios estudios respaldan su uso como complementos de las reparaciones primarias y de las reconstrucciones de brecha mediante aloinjertos (18,21,26,27) . Funcionan como una barrera física entre el nervio reparado y el entorno externo, que protege y contiene las proteínas de la matriz extracelular necesarias para una curación óptima en el sitio de reparación, así como para prevenir el crecimiento excesivo y el escape axonal (28,29,30,31,32) .…”
Section: Bibliografíaunclassified
“…Current methods use virtual surgical planning sessions and custom plate milling via third-party vendors, which is costly and time-consuming, negating the effectiveness in acute facial trauma. This technical note describes a state-of-the-art inhouse expedited digital workflow for computer-aided virtual fracture reduction, 3 undoubtedly stood the test of time; however, computer-aided design (CAD) and computer-aided manufacturing (CAM) are providing methods that are changing the way oral and maxillofacial surgery is completed.1, 2, 3, 4 Considering that surgeons now have the ability to preplan and enhance execution, many are using CAD-CAM as their go-to method in orthognathic surgery, craniofacial surgery, and microvascular surgery.5, 6, 7 Operating room (OR) costs have and will always be a major concern;…”
mentioning
confidence: 99%